Response of air stagnation frequency to anthropogenically enhanced radiative forcing - Horton, Daniel E. (2012)
Stagnant atmospheric conditions can lead to hazardous air quality by allowing ozone and particulate matter to accumulate and persist in the near-surface environment. By changing atmospheric circulation and precipitation patterns, global warming could alter the meteorological factors that regulate air stagnation frequency. We analyze the response of the National Climatic Data Center (NCDC) Air Stagnation Index (ASI) to anthropogenically enhanced radiative forcing using global climate model projections of late-21(st) century climate change (SRES A1B scenario). Our results indicate that the atmospheric conditions over the highly populated, highly industrialized regions of the eastern United States, Mediterranean Europe, and eastern China are particularly sensitive to global warming, with the occurrence of stagnant conditions projected to increase 12-to-25% relative to late-20(th) century stagnation frequencies (3-18+ days/year). Changes in the position/strength of the polar jet, in the occurrence of light surface winds, and in the number of precipitation-free days all contribute to more frequent late-21(st) century air mass stagnation over these high-population regions. In addition, we find substantial inter-model spread in the simulated response of stagnation conditions over some regions using either native or bias corrected global climate model simulations, suggesting that changes in the atmospheric circulation and/or the distribution of precipitation represent important sources of uncertainty in the response of air quality to global warming.